2013
DOI: 10.1089/jpm.2012.0569
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Depression in Patients Receiving Specialist Community Palliative Care: Does Using a Single Screening Question Identify Depression Otherwise Diagnosed by Clinical Interview?

Abstract: Background: Depression affects a quarter of palliative patients and is associated with reduced quality of life. Screening for psychological problems at key points in the patients' pathway is recommended but there is no consensus as to how to do this. Aims: The study's aim was to assess the efficacy of a screening question for depression against a semistructured interview in patients referred to a specialist community palliative care team. Methods: Fifty community palliative care patients were assessed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A single-item screening tool ("Are you feeling depressed?") has been shown to be useful for identifying depression (80). Both antidepressants and psychotherapy have shown efficacy in treating depression in patients with advanced malignancies (81,82).…”
Section: Psychosocial and Existential Distressmentioning
confidence: 99%
“…A single-item screening tool ("Are you feeling depressed?") has been shown to be useful for identifying depression (80). Both antidepressants and psychotherapy have shown efficacy in treating depression in patients with advanced malignancies (81,82).…”
Section: Psychosocial and Existential Distressmentioning
confidence: 99%
“…performed poorly in three later studies among patients with advanced cancer. [24][25][26] In contrast to these findings, Taylor et al 27 found good screening capabilities by use of the main criterion on lowered mood for MDE. The question 'Have you felt depressed most of the day, nearly every day, for two or more weeks?'…”
Section: Screening For Depressionmentioning
confidence: 88%
“…23 The single item ‘Are you depressed?’ performed poorly in three later studies among patients with advanced cancer. 2426 In contrast to these findings, Taylor et al 27 found good screening capabilities by use of the main criterion on lowered mood for MDE. The question ‘Have you felt depressed most of the day, nearly every day, for two or more weeks?’ identified MDD assessed by a structured interview with a sensitivity of 0.80 and a specificity of 0.85.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation